The use of vocabulary learning strategies in an MMORPG among Southeast Asian ESL players - Afendi Hamat,; Muhammad Farkhan Imran Mahamad Amran, (Penerbit Universiti Kebangsaan Malaysia, 2021)
This paper describes a study on the Vocabulary Learning Strategies (VLS) used by players from Southeast Asia in an MMORPG called Final Fantasy XIV. The objective is to identify the strategies the players used and their opinions of the game as a platform to assist their vocabulary learning. Fifty players who met the requirements of the study were selected and a survey was administered via a questionnaire (Cronbach’s Alpha values 0.824 and 0.758). The results were analyzed using descriptive statistics. Results showed that Activation Strategies were the most preferred strategy while Cognitive Strategies were the least preferred. The players also reported a generally favorable opinion of the game as a method to learn and acquire English vocabulary. MMORPGs have been shown to be a viable tool for informal language learning and a suggestion is made on how language teachers may take advantage of this.